Investigating fan interaction, influencer endorsements, and quality content as determinants of brand loyalty in Malaysian e-Sports / Muhammad Danial ‘Immran ... [et al.] - ‘Immran, Muhammad Danial; Linoby, Adam; Md Yusoff, Yusandra; Haziq, Amrun; Zulqarnain, Muhammad; Sazali, Razif (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Social media marketing plays a pivotal role in shaping brand equity, yet its impact within the esports industry remains underexplored. This study examines the relationship between social media marketing and brand equity [1], focusing on Gamesbond Malaysia. Addressing gaps in Malaysian esports research, it provides critical insights into consumer perceptions and brand-building strategies. A quantitative survey was conducted with 235 respondents to examine social media marketing's influence on brand equity among Gamesbond consumers. Respondents, predominantly young adults were selected to represent diverse demographics. Descriptive statistics, Spearman correlation and regression analysis were used to analyze collected data, focusing on the effect of strategic marketing factors towards brand equity dimensions by using Jamovi Software.